Dynamics of Underactuated Multibody Systems Modeling, Control and Optimal Design - Seifried, Robert; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
Underactuated multibody systems are intriguing mechatronic systems, as they possess fewer control inputs than degrees of freedom. Some examples are modern light-weight flexible robots and articulated manipulators with passive joints. This book investigates such underactuated multibody systems from an integrated perspective. This includes all major steps from the modeling of rigid and flexible multibody systems, through nonlinear control theory, to optimal system design. The underlying theories and techniques from these different fields are presented using a self-contained and unified approach and notation system. Subsequently, the book focuses on applications to large multibody systems with multiple degrees of freedom, which require a combination of symbolical and numerical procedures. Finally, an integrated, optimization-based design procedure is proposed, whereby both structural and control design are considered concurrently. Each chapter is supplemented by illustrated examples.
1 Introduction -- 2 Multibody Systems -- 3 Feedback Linearization and Model Inversion of Nonlinear Systems -- 4 Trajectory Tracking of Multibody Systems -- 5 Model Inversion Using Servo-Constraints -- 6 Trajectory Tracking of Flexible Multibody Systems -- 7 Optimal System Design -- 8 Concluding Remarks -- Index.
Keywords: Vibration; Dynamical systems; Dynamics; Control engineering; Robotics; Mechatronics; Mechanics; Vibration, Dynamical Systems, Control; Control, Robotics, Mechatronics; Classical Mechanics